Philosophy and friendship - Lynch, Sandra (Edinburgh University Press, 2005)
A philosophical exploration of the meaning and significance of friendship. This book explains the persistence of friendship today in the light of the history of philosophical approaches to the subject. It considers ideals of intimacy and fusion in the context of claims that such ideals are unrealistic and even dangerous. Cicero's scepticism about friendship in the public realm is compared with the Aristotelian view of friendship as a genuine political bond, and with Derrida's development of that view via an exploration of Aristotle's alleged and provocative announcement 'O my friends, there is no friend'. Tensions between love and respect, identity and difference, a focus on the self and a focus on the other are closely examined. From Aristotle to contemporary theorists, the book explores the conditions that enable the development of self-understanding in friendship, the delicate and unstable pairing of concepts like inclination and duty and distinctions between self-love, self esteem and self-concern in relations between friends. Key Features Recognition of the variety of the term 'friend' in the history of philosophy The treatment of the tension between identity and difference in relations between friends Discussion of the contribution of friendship to self-understanding.